The Influence of Activity, Interest, Opinion (AIO), and Price Perception on the Decision to Watch a Film in the Cinema - Djamaly, Muhammad Fadheel; Djumarno, Djumarno; Astini, Rina; Asih, Daru (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research was conducted because of a shift and decline in audience interest in watching films at the Puri XXI cinema after the emergence of competitors in West Jakarta. These changes are influenced by factors such as lifestyle and price perception. This research aims to examine the relationship between activity, interest, opinion (AIO), price perception, and consumer decisions to watch films at the Puri XXI Cinema, South Jakarta. The research sample consisted of 100 respondents selected using non-probability sampling techniques. Linear regression analysis and significance tests were carried out with the help of SPSS 17.0 software to test the hypothesis. The research results show that partially, the activity variable does not have a significant influence on consumers' viewing decisions. However, the interest and opinion variables, although they do not have a strong influence, still positively influence viewing decisions. Price perception also has the largest positive and significant influence on viewing decisions. Overall, the activity, interest, opinion, and price perception variables together have an influence of 48.1% on consumers' viewing decisions.